UNIVERSAL DESIGN – SOCIAL, PEDAGOGICAL AND MANAGERIAL CHALLENGE (Innovation in Woodworking Industry and Engineering design, 2026)
Universal design (UD) as a concept of consideration rather than an afterthought that may lead to subsequent adaptations – following the principle of early intervention to address the cause, rather than the symptom. It enforces and empowers everyone to play a full role in society. Individually and mutually, professionally and secularly, UD should fly inspirationally above all social areas. A physical platform which allows to be complemented by practical and emotional learning, that fights stereotypes and prejudices and examines the limits of normality by defining difference as the new normal – is excellent example for Universal design. So, Universal design is the natural way things happen for everyone. Therefore, it should preferably be possible to influence, to attract and invite ideas leading to something everyone can agree with and something that comforts all in own understanding of successful living and prosperity.